If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 = 2(x + 3) Reorder the terms: 3 + 4x = 2(x + 3) Reorder the terms: 3 + 4x = 2(3 + x) 3 + 4x = (3 * 2 + x * 2) 3 + 4x = (6 + 2x) Solving 3 + 4x = 6 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 4x + -2x = 6 + 2x + -2x Combine like terms: 4x + -2x = 2x 3 + 2x = 6 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 2x = 6 + 0 3 + 2x = 6 Add '-3' to each side of the equation. 3 + -3 + 2x = 6 + -3 Combine like terms: 3 + -3 = 0 0 + 2x = 6 + -3 2x = 6 + -3 Combine like terms: 6 + -3 = 3 2x = 3 Divide each side by '2'. x = 1.5 Simplifying x = 1.5
| x^3+8x^2+16=0 | | (x+5)/8=-1/2x | | 4+4x=25x+x | | 6r+-1+6r=11 | | -3x^2+16x=0 | | 5x-1=4(x+1) | | 3(-2+x)=6+3x | | -18+6=-4(x+6) | | 20t-15=18x-7 | | 6x-2=2(2x+6) | | 2222+m=35 | | 9x-4=5(2x-3) | | 3x+4x=-x+7m | | -1.2y+.8=-.76 | | 7x+1=2(2x+2) | | 44+m=35 | | h(t)=-16t^2+122t+10 | | 6x-1=4(x-1) | | 4+m=35 | | .5x+.07=.25x+.57 | | -7/13p=-4 | | x^4-4x^3-30x^2-8x-64=0 | | 4x-2=102 | | -6n+-2=16 | | 5r(8r-5)(5r-1)=0 | | 3+8X= | | 19x-5=11x-21 | | 4x+10=3(2x+5) | | 5(12w+1)= | | 16-3.4d=-8 | | 9+3=612 | | 7x+2=3(3x+1) |